The sclerosing sertoli cell tumor of the testis: a case report - Xueyao Tang; Yifan Hu; Hong Zhou; Yang Zhou (BMC, 2023)
Abstract Background Testicular Sertoli cell tumor (SCT) is very rare sex cord-gonadal stromal tumor, and sclerosing SCT (SSCT) is even rarer. So far, no more than 50 cases of SSCT have been reported. 80% of SSCTs are less than 2 cm in diameter, large volume mass is pretty unusual. SSCT is usually benign with very low malignant potential. However, it is easily misdiagnosed as a malignant tumor resulting in the removal of the entire testicle. Case presentation A 55-year-old Chinese male patient presented with a six months' history of right testis progressively enlargement and negative tumor markers. The physical examination was nothing special except for swelling in the right testicle. Imaging identified a large mass in right testicle with rich blood. A right radical orchiectomy was performed on suspicion of malignancy. However, the tumor was postoperatively diagnosed as SSCT, which pathologically consisted of a tubular pattern with regular nuclei and embedded in a densely collagenous stroma, as well as diffusely positive for vimentin, β-catenin and synaptophysin. After 7 months of follow up, no evidence of local recurrence and metastasis has been observed. Conclusion This rare case is helpful to expand the knowledge of the testicular tumor and alert us fully understand the rare variant of SCTs in order to choose the optimal management when they encounter SSCT.